The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-019-52220-7
|View full text |Cite|
|
Sign up to set email alerts
|

Gamma Attenuation Coefficients of Nano Cadmium Oxide/High density Polyethylene Composites

Abstract: In the present work, high density polyethylene (HDPE) matrix mixed with micro-sized and nano-sized Cadmium oxide (CdO) particles of different concentrations were prepared by compression molding technique. The aim of the study is to investigate the effect of particle size and weight percentage of CdO particles on the gamma radiation shielding ability of CdO/HDPE composites. The mass attenuation coefficients of pure HDPE, micro-CdO/HDPE and nano-CdO/HDPE composites were evaluated at photon energies ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 22 publications
2
64
0
Order By: Relevance
“…Nanogadolinium oxide (Gd 2 O 3 ) composites were more efficient in shielding X- and gamma ray than microgadolinium oxide (Gd 2 O 3 ) composites, and an enhanced effect of ~ 28% was obtained with gadolinium oxide (Gd 2 O 3 ) content of around 5 weight percent at 59.5 keV (Li et al 2017 ). The addition of micro- and nanocadmium oxide (CdO) particles to the high-density polyethylene matrix increased the mass attenuation coefficients of the composites mainly at low gamma-ray energies (El-Khatib et al 2019 ). The polymer–matrix composites based on high-density polyethylene with either lead oxide (PbO) nanoparticles or lead oxide bulk using 10 and 50% weight fractions synthesized by solid-state intermixing and thermal pressing technique showed interesting gamma-rays shielding properties especially for high filler loadings (Mahmoud et al 2018a , b ).…”
Section: Polymer Composites For Gamma-radiation Shieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanogadolinium oxide (Gd 2 O 3 ) composites were more efficient in shielding X- and gamma ray than microgadolinium oxide (Gd 2 O 3 ) composites, and an enhanced effect of ~ 28% was obtained with gadolinium oxide (Gd 2 O 3 ) content of around 5 weight percent at 59.5 keV (Li et al 2017 ). The addition of micro- and nanocadmium oxide (CdO) particles to the high-density polyethylene matrix increased the mass attenuation coefficients of the composites mainly at low gamma-ray energies (El-Khatib et al 2019 ). The polymer–matrix composites based on high-density polyethylene with either lead oxide (PbO) nanoparticles or lead oxide bulk using 10 and 50% weight fractions synthesized by solid-state intermixing and thermal pressing technique showed interesting gamma-rays shielding properties especially for high filler loadings (Mahmoud et al 2018a , b ).…”
Section: Polymer Composites For Gamma-radiation Shieldingmentioning
confidence: 99%
“…Latterly, investigators working in the field of radiation protection have focused and reported numerous polymer matrices that can be used as gamma-ray shields like bismuth oxide (Bi 2 O 3 ) filled poly (methyl methacrylate) composites; high-density polyethylene (HDPE) composite loaded with tungsten (W), molybdenum sulfide (MoS 2 ), and boron carbide (B 4 C); micro- and nanosized tungsten oxide (WO 3 ) dispersed emulsion polyvinyl chloride (EPVC) polymer composites; lead oxide filled isophthalic resin polymer composites; silicone rubber composites containing bismuth content; polymer bricks (PolyBiz); polyester composites reinforced with zinc; composites of high-density polyethylene with zinc oxide; lead oxide; and cadmium oxide (Plionis et al 2009 ; El-Fiki et al 2015 ; Aghaz et al 2016 ; Mahmoud et al 2018a , b ; Afshar et al 2019 ; Alsayed et al 2019 , 2020 ; El-Khatib et al 2019 ; Cao et al 2020 ; Kaçal et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… Shielding material Polymer Attenuation coefficient (cm −1 ) HVL (cm) Ref. Water 0.06323 10.96 29 Ordinary concrete 0.13342 5.19 29 Bi 2 O 3 Nature rubber 0.105 7 30 Bi 2 O 3 Polyvinyl alcohol 0.127 5.475 20 CdO High density polyethylene 0.104 6.67 31 Pb 3 O 4 Phenyl epoxy 0.103 6.74 32 PbO 2 Polyacrylamide 0.1343 5.16 This work …”
Section: Resultsmentioning
confidence: 99%
“…Poly mer com pos ites re in forced by in or ganic metal ox ides were widely stud ied as pro tec tive ra di ation shield ing ma te ri als. In the lit er a ture, many polymers such as poly eth yl ene [5], re cy cled poly eth yl ene [6], ep oxy [7], poly es ter [8], sty rene bu ta diene rub ber [9], eth yl ene-pro pyl ene-dine mono mer (EPDM) [10], polyimide [11], nat u ral rub ber [12] and poly sty rene [13] were in ves ti gated as ra di a tion shield ing ma trixes. Var i ous metal ox ides like PbO [8], PbWO 4 [10], Sm 2 O 3 [11], WO 3 [14], Bi 2 O 3 [15] and Gd 2 O 3 [3], with dif fer ent par ti cle sizes, were used as fill ers in the poly meric ma trix to shield X-rays [16] and g-rays.…”
Section: Introductionmentioning
confidence: 99%
“…El-Khatib et al [5] stud ied the ef fect of mi croand nano-cad mium ox ide (CdO) par ti cles, of dif fer ent load ings dis persed in high den sity poly eth yl ene (HDPE) on the g-rays trans mis sion, rang ing from 59.53 keV to 1480.01 keV and found that the CdO parti cles were more ef fec tive to at ten u ate g-rays spe cially at lower pho ton en er gies. Hence, the aim of this in ves -ti ga tion is to pres ent a com par a tive study be tween CdO and PbO ac cord ing to their sizes as fill ers, in HDPE poly meric ma trix for gamma-ra di a tion shielding ap pli ca tions.…”
Section: Introductionmentioning
confidence: 99%